DIGITAL STRATEGIES FOR IMPROVING GOVERNMENT PERFORMANCE ACCOUNTABILITY THROUGH PERFORMANCE INFORMATION SYSTEMS AT THE MEDAN CENTER FOR FOOD AND DRUG CONTROL - Leonardo Simamarta; Tunggul Sihombing; Asima Yanty Sylvania Siahaan (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This thesis aims to analyze the implementation of the Government Agency Performance Accountability System (SAKIP) policy and its implications for organizational performance accountability at the Central Office for Drug and Food Control (BBPOM) in Medan. This study was motivated by the fact that the Government Agency Performance Accountability (AKIP) score of the BBPOM in Medan remains in the “BB” category and has not yet reached the national target of the “A” or “AA” categories. The research method used was descriptive qualitative, with data collection techniques involving in-depth interviews and documentation. The research analysis utilized George C. Edward III’s policy implementation theory, which encompasses four main variables: communication, resources, disposition, and bureaucratic structure. The results indicate that SAKIP implementation remains suboptimal, particularly regarding the understanding of outcome-based performance, limitations in human resource competencies, and the lack of a strong performance-based work culture. Additionally, coordination and consistency in procedure implementation remain significant challenges. This study concludes that improvements in AKIP scores are largely determined by the overall quality of policy implementation; therefore, strengthening organizational capacity and sustainable performance management is necessary.